2018
DOI: 10.3389/fpls.2018.00153
|View full text |Cite
|
Sign up to set email alerts
|

Internal and External Dispersal of Plants by Animals: An Aquatic Perspective on Alien Interference

Abstract: Many alien plants use animal vectors for dispersal of their diaspores (zoochory). If alien plants interact with native disperser animals, this can interfere with animal-mediated dispersal of native diaspores. Interference by alien species is known for frugivorous animals dispersing fruits of terrestrial plants by ingestion, transport and egestion (endozoochory). However, less attention has been paid to possible interference of alien plants with dispersal of diaspores via external attachment (ectozoochory, epiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 94 publications
0
12
0
1
Order By: Relevance
“…In this study, we found that epizoochory in parrots adds a new example of understudied animal-mediated dispersal mode [ 15 ] that challenges our understanding of this dispersal syndrome in several ways. First, epizoochory is generally considered infrequent compared to other zoochory mechanisms such as endozoochory (i.e., dispersal of viable seeds after gut passage), as it is mostly caused by the eventual attachment of propagules to the body of mammals or some bird species [ 11 , 16 , 17 , 34 ]. These plant–animal interactions are not considered mutualistic, as adhered fruits do not provide dispersal agents with a nutritional reward [ 11 , 16 ], with the only exception of some extremely rare events of epizoochory in songbirds [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that epizoochory in parrots adds a new example of understudied animal-mediated dispersal mode [ 15 ] that challenges our understanding of this dispersal syndrome in several ways. First, epizoochory is generally considered infrequent compared to other zoochory mechanisms such as endozoochory (i.e., dispersal of viable seeds after gut passage), as it is mostly caused by the eventual attachment of propagules to the body of mammals or some bird species [ 11 , 16 , 17 , 34 ]. These plant–animal interactions are not considered mutualistic, as adhered fruits do not provide dispersal agents with a nutritional reward [ 11 , 16 ], with the only exception of some extremely rare events of epizoochory in songbirds [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the unique fruit manipulation abilities of parrots, using their large and mobile beaks, their tongues, and their feet for feeding [ 25 ], may facilitate high rates of seed attachment through pulp residues of fleshy fruits, viscid mucilages, and seeds with specialized structures for anemochory that easily adhere on their body surfaces. Finally, coinciding with typical epizoochory syndromes [ 11 , 16 ], parrots may perform directed dispersal by moving seeds far from the mother plant to similar habitats where germination is feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In New Zealand, introduced blackbirds ( Turdus merula ) and song thrushes ( T. philomelos ) dispersed more seeds than native frugivorous avifauna within secondary forested areas ( Wyman & Kelly, 2017 ; but see Macfarlane, Kelly & Briskie, 2016 ). However, alien plants can also disperse by endozoochory and this could have negative consequences for native biodiversity and ecosystem functions ( Reynolds, Miranda & Cumming, 2015 ; Green, 2016 ; Van Leeuwen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the invasive antdispersed South African shrub Polygala myrtifolia outcompeted native plant species for seed dispersal services by ants (Rowles and O'Dowd, 2009). However, competition for seed dispersal services may not necessarily result in negative outcomes for native species if these benefit from the additional dispersers brought into the area by the resources provided by alien plant species (van Leeuwen, 2018).…”
Section: Consequences Of Alien Plant Species On Urban Dispersal Networkmentioning
confidence: 99%